Expanding the boundaries of ligand–target modeling by exascale calculations - Bolnykh, Viacheslav; Rossetti, Giulia; Rothlisberger, Ursula; Carloni, Paolo (Wiley interdisciplinary reviews. Computational molecular science, 2021)
Molecular simulations and molecular docking are widely used tools to investigate ligand/target interactions and in drug design. High‐performance computing (HPC) is boosting both the accuracy and predictive power of these approaches. With the advent of exascale computing, HPC may become standardly applied in many drug design campaigns and pharmacological applications. This review discusses how innovative HPC algorithms and hardware are being exploited in current simulations and docking codes, pointing also at some of the limitations of these approaches. The focus is on technical aspects which might not be all that familiar to the computational pharmacologist. This article is categorized under: Software > Molecular Modeling Software > Simulation Methods Structure and Mechanism > Computational Biochemistry and Biophysics High‐performance computing in the upcoming exascale era will accelerate tremendously computer‐aided drug design.